The Dayaks’ Food Taboos: Their Meanings and Functions for the Tariu Borneo Bangkule Rajakng Members - Agnes Monika; Syarmiati Syarmiati; Dwi Surti Junida; Adityo Darmawan Sudagung (Jurnal Dialog, 2026)
Studies on food taboos are mainly discussed within the context of pregnancy. There is less focus on the relationship between practices and ethnic groups. TBBR, as one of the Dayak organisations, requires its members to perform food taboos. These are believed to be a vital part of Dayak culture and spirituality, inherited through generations, serving as a code of conduct, a protector of spiritual harmony, and a marker of cultural identity. This ethnographic study aims to identify food taboo practices, their contributing factors, and their impact on members of the Tariu Borneo Bangkule Rajakng (TBBR) Organisation. The analysis reveals that food taboos within TBBR are not only related to physical health but also function as spiritual rituals to gain strength and immunity, as well as to connect the present people with their ancestors. In addition, these taboos reinforce discipline, promote solidarity, and affirm the Dayak cultural identity. In conclusion, the practice of food taboos in TBBR is a complex tradition that integrates spiritual, physical, and social aspects, aiming to preserve the ancestral cultural heritage in the modern era.